2012
DOI: 10.1016/j.jbiomech.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low pass filtering on joint moments from inverse dynamics: Implications for injury prevention

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Kristianslund, E., Krosshaug, T., van den Bogert, A. J. (2012) Hz. The results revealed significant differences, especially between conditions with different filtering of force and movement. Mean (SD) peak knee abduction moment for the 10-10 and 10-50 condition were 1.27 (0.53) and 1.64 (0.68) Nm/kg, respectively. Ranking of players based on knee abduction moments were affected by filtering condition. Out of 20 players wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
246
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 405 publications
(252 citation statements)
references
References 22 publications
4
246
2
Order By: Relevance
“…If the kinetic data are filtered at a higher cut-off frequency than the kinematic data, and the cut-off frequency applied to the kinematic data is lower than the highest frequencies found in the true kinematic signal, then excessive fluctuations in the RJM will be produced around impact. Whilst previous studies have identified similar phenomena in landings and cutting manoeuvres 12,13 , these have only been investigated using one or two widely mismatched cut-off frequencies. The data presented in the current study extend these findings to the analysis of gait, whilst further highlighting that even relatively small mismatches between the cut-off frequencies applied to the kinetic and kinematic data affect the calculated RJM at the knee joint, and that these effects are not necessarily dependent on the absolute values of the cut-off frequencies that are chosen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the kinetic data are filtered at a higher cut-off frequency than the kinematic data, and the cut-off frequency applied to the kinematic data is lower than the highest frequencies found in the true kinematic signal, then excessive fluctuations in the RJM will be produced around impact. Whilst previous studies have identified similar phenomena in landings and cutting manoeuvres 12,13 , these have only been investigated using one or two widely mismatched cut-off frequencies. The data presented in the current study extend these findings to the analysis of gait, whilst further highlighting that even relatively small mismatches between the cut-off frequencies applied to the kinetic and kinematic data affect the calculated RJM at the knee joint, and that these effects are not necessarily dependent on the absolute values of the cut-off frequencies that are chosen.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that during activities with high impact forces, filtering the kinetic and kinematic input data using different cut-off frequencies could lead to the computation of artificial peaks in the determined RJMs [11][12][13] . It is thus possible that previously observed excessive fluctuations in the knee RJM during early stance in sprinting are influenced by the digital filtering procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-seven reflective markers were attached over anatomical landmarks on the legs, arms and torso [18]. One experienced physiotherapist, with several years practice for marker placement, was employed for skin marker placement in both sessions.…”
Section: Design and Protocolmentioning
confidence: 99%
“…DVJ, side cutting, hopping, single leg landings. Whilst samples may be difficult to standardize given that most recruitment is governed by convenience, the choice of task and biomechanical methods, which can significantly affect the KAA and KAM [69,[72][73][74][75], could be standardized. The DVJ task is frequently chosen as it replicates the task from the prospective evidence [28].…”
Section: Extrapolation and Standardizationmentioning
confidence: 99%